208k views
5 votes
Solve:
6(-x- 3) = 24
X=

User ZaSter
by
4.6k points

2 Answers

5 votes

Answer:

X= -7

Explanation:

Divide both sides of the equation by 6.

Move the constant to the right.

Add the numbers.

Change the signs.

User Antejan
by
5.3k points
3 votes

Answer:

x = -7

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define

6(-x - 3) = 24

Step 2: Solve for x

  1. Divide 6 on both sides: -x - 3 = 4
  2. Add 3 on both sides: -x = 7
  3. Divide -1 on both sides: x = -7

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: 6(-(-7) - 3) = 24
  2. Multiply: 6(7 - 3) = 24
  3. Subtract: 6(4) = 24
  4. Multiply: 24 = 24

Here we see that 24 does indeed equal 24.

∴ x = -7 is the solution to the equation.

User David Richards
by
4.6k points